ANALISIS KEBIJAKAN PENDIDIKAN DALAM CARA PANDANG MADRASAH - Mufasirul Bayani (ADIBA : JOURNAL OF EDUCATION, 2024)
Madrasahs have a strategic role in national development. Currently, madrasah education is still considered "second class" education. This is because the implementation of madrasahs still faces a number of major problems, starting from management issues and the low quality of madrasah education. This article is intended to provide an overview of the role of madrasahs in the education system in Indonesia, madrasah problems, opportunities, and challenges for madrasahs. Madrasahs have become part of the national education system. The method used in this study is a literature study by collecting secondary data from various sources of books and journals, then conducting a descriptive analysis of the data presented in detail. Various problems faced by madrasahs include education management, the gap between state and private, the quality of madrasahs, to the opportunities and challenges for madrasahs in Indonesia today.